Inovasi Pembelajaran Morfologi Bahasa Arab pada Tashrif Lughawi dengan Finger Gymnastic - Moh. Ali Qorror Al-Khasy; Kamal Yusuf (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract, in response to the emergence of revolution industry 4.0 in education, there have been lots of innovations in teaching in the field of education, especially in teaching of Arabic. This research was conducted to actively answer to this phenomenon. This article focuses on innovation aspect of the method used in teaching of Arabic morphology or what traditionally so called ilm sharf. Many learners of Arabic still have perception that learning Arabic is challenging and difficult. As a result, an innovative method has been developed to help learners in teaching Tashrif Lughawi using finger gymnastic method. This study demonstrated that the adaptation of the method into classroom learning and teaching can attract students’ attention to learn Arabic. The implementation in using the finger gymnastic also revealed that this method enables learners to understand and memorise easily and quickly the Arabic words paradigm. Furthermore, integrating this method can also improve the language skills which include listening, reading, and writing. Keywords: Innovation, Arabic Morphology, Finger Gymnastic, Tashrif